THE SYNERGY OF AGILE APPROACH AND LOW-CODE TECHNOLOGIES AS A DRIVER OF ENTERPRISE ADAPTABILITY UNDER CRISIS CONDITIONS (Development Service Industry Management, 2025)
This article explores modern approaches to ensuring the continuity of digital business operations in high-risk environments, particularly during wartime and under conditions of economic uncertainty. It presents an interdisciplinary analysis of the synergistic integration of three essential components of contemporary innovation management: Agile methodologies, low-code development platforms, and cloud technologies. The author argues that the comprehensive implementation of these tools enables organizations to rapidly adapt to dynamic external conditions, reduce time-to-market and resource costs for digital service delivery, and enhance the resilience of business processes.Special attention is given to practical case studies from international and Ukrainian companies, particularly within the context of limited infrastructure access, IT talent shortages, and team relocation. The role of cloud infrastructure in supporting fault-tolerant digital services is emphasized, along with the importance of telemetry tools for managerial monitoring, evaluating feature adoption, and enabling data-driven strategic decision-making. The empirical component includes an assessment of key effectiveness metrics such as Time-to-Market, Velocity, Defect Rate, and Customer Satisfaction (CSAT), which quantitatively confirm the benefits of the integrated approach. The article also identifies managerial mechanisms for maintaining digital resilience, including adaptive planning, the use of KPIs, telemetry-based insights, and the implementation of OKR frameworks in Agile teams. Based on the findings, practical recommendations are proposed for enterprise leaders considering the adoption of low-code platforms in combination with Agile practices and cloud infrastructure, aiming to reduce technology dependency, accelerate digital transformation, and strengthen economic security in turbulent conditions.
Keywords: digital transformation; low-code; Agile management; cloud technologies; economic security; business continuity; managerial adaptability; innovation management; telemetry